1997
DOI: 10.1111/j.2044-835x.1997.tb00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' and fathers' scaffolding of their 2‐year‐olds during problem‐solving and literacy interactions

Abstract: Building upon Wood & Middleton's (1975) concept of parental scaffolding, the influence of parent-child interactions on children's competence within several tasks was investigated. Thirty-two 2-year-old children visited our lab twice, once with their mothers and once with their fathers. During each session dyads participated in problem-solving and literacy tasks, followed by independent child performance tasks. Although subtle differences were found between mothers' and fathers' contingent behaviours displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 22 publications
4
61
0
Order By: Relevance
“…This also supports the findings of past research that parents provide sensitive scaffolding and guidance to their children in various types of tasks (e.g., Connor and Cross, 1993;Connor et al, 1997;Pratt et al, 1992).…”
Section: Discussionsupporting
confidence: 85%
“…This also supports the findings of past research that parents provide sensitive scaffolding and guidance to their children in various types of tasks (e.g., Connor and Cross, 1993;Connor et al, 1997;Pratt et al, 1992).…”
Section: Discussionsupporting
confidence: 85%
“…There is evidence that positive paternal interactions during a child's second and third years contribute significantly to the child's cognitive and linguistic development (Shannon, Tamis-LeMonda, London, & Cabrera, 2002;Tamis-LeMonda, Shannon, Cabrera, & Lamb, 2004). Indeed, sensitive and responsive fathering promotes cognitive and socioemotional development comparable to such high-quality mothering (Conner, Knight, & Cross, 1997;Easterbrooks & Goldberg, 1984;Van Ijzendoorn & DeWolff, 1997). One might expect, therefore, that fathers modify their actions in ways that support infant learning and development.…”
Section: Fathers' Role In Infants' Developmentmentioning
confidence: 92%
“…One study found qualitative characteristics of father involvement (e.g., behavioral sensitivity) to be associated with toddlers' problem solving . Fathers' scaffolding during teaching interactions predicted problem solving and literacy skills in 2-year-old children (Conner, Knight, & Cross, 1997). A recent study of low-income African American fathers and their 3-year-olds indicated that fathers who were nurturant during play had children with better cognitive and language competencies (Black et al, 1999).…”
Section: Beyond Rough and Tumble: Fathers' Effects On Toddlersmentioning
confidence: 98%